Elsevier's CiteScore index values for Acta Dermatovenerologica Alpina, Pannonica et Adriatica - Šterbenc, Anja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2017)
Elsevier's recently launched citation metric CiteScore enables comprehensive, transparent, and current evaluation of a journal's performance. For an editorial office, insight into a journal's impact over time is of great value when making important decisions regarding the journal's future. A 2016 update of CiteScore index values for Acta Dermatovenerologica Alpina, Pannonica et Adri- atica (Acta Dermatovenerol APA) showed a slight decrease in the CiteScore index value from 1.18 in 2015 to 0.96 in 2016. Acta Dermatovenerol APA can still be considered the principal journal in the field of dermatology and sexually transmitted infections in our region, with almost half of the articles published between 2013 and 2015 cited at least once in 2016. Acta Dermatovenerol APA performed well in both categories listed because it ranked 67th out of 121 journals in the category Dermatology (44th percentile) and 175th out of 250 journals in the category Infectious Diseases (30th percentile).
Keywords: academic journals; akademske revije; citation; citiranje; dermatologija; dermatology